Analisis Usaha Ternak Ayam Broiler Di Kandang Kampus Polilaman Selama Satu Kali Masa Produksi - Astuti, Erlina (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to find out and analyze the broiler chicken farming business for one production period. The type of data used in this study is quantitative data, namely data in the form of numbers, which are related to the aspect of revenue (sales of production products) and expenses during the production process, both fixed costs such as the cost of depreciation of cages and equipment and others as well as non-fixed costs (variable costs) such as the cost of production facilities (chicken seeds, feed and medicines). the cost of litter materials and others. This component of revenue and expense will be used to calculate income or profit in the broiler chicken farming business. The data obtained were then analyzed descriptively to describe the business conditions and characteristics of farmers, the composition of production costs, revenue and income of broiler farming businesses. From the results of the study, it can be concluded that the broiler farming business of the POLILAMAN campus with a business scale of 100 heads provides a considerable profit or income, namely - (rupiah) per production period for 35 days.